2005
DOI: 10.1002/pmic.200401252
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fragile X mental retardation‐1 gene with nuclear export signal mutation changes the expression profiling of mouse cerebella immortal neuronal cell

Abstract: Fragile X syndrome (FXS) is the most frequent cause of inherited mental retardation and is largely caused by a loss of expression of fragile X mental retardation protein (FMRP), encoded by fragile X retardation gene-1 (Fmr1). FMRP is a multifunction protein, with intrinsic RNA-binding properties, which is a component of ribonucleoprotein complex associated with polyribosomes. The properties of FMRP indicate that it might participate in post-transcriptional processes in the regulation of some mRNA species, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Several experiments have shown that FMRP without a NES (FMRP-NES) accumulates in the nucleus in different cell lines (Fridell et al, 1996; Hu et al, 2005; Tamanini et al, 1999a; Willemsen et al, 1996), although some studies also have shown the presence of small quantities of FMRP-NES in the cytoplasm (Kim et al, 2009). Fmr1 KO neurons transfected with EGFP-FMR1_Iso12 showed a predominantly nuclear localization, while the dendrites did not show dendritic EGFP-FMRP_Iso12-positive RNA-granules.…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments have shown that FMRP without a NES (FMRP-NES) accumulates in the nucleus in different cell lines (Fridell et al, 1996; Hu et al, 2005; Tamanini et al, 1999a; Willemsen et al, 1996), although some studies also have shown the presence of small quantities of FMRP-NES in the cytoplasm (Kim et al, 2009). Fmr1 KO neurons transfected with EGFP-FMR1_Iso12 showed a predominantly nuclear localization, while the dendrites did not show dendritic EGFP-FMRP_Iso12-positive RNA-granules.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies in FXS animal models have indeed provided evidence for alterations of several proteins associated with the central nervous system [53][54][55][56][57]. In a FXS mouse cerebellum cell the expression of the fragile X mental retardation protein (FMRP) was altered, creating a model for cellular deficits found in FXS.…”
Section: Fragile X Syndromementioning
confidence: 99%
“…In a FXS mouse cerebellum cell the expression of the fragile X mental retardation protein (FMRP) was altered, creating a model for cellular deficits found in FXS. The investigators found 56 proteins differentially expressed in the transfected cells, including 16 proteins whose levels were decreased and 40 whose levels were increased [53]. Using SILAC, a study of primary neuronal culture taken from an FXS knock-out mouse demonstrated changes in more than 100 proteins, many of which were associated with nervous system function [58].…”
Section: Fragile X Syndromementioning
confidence: 99%
“…3-B A superexpressão da FMRP recombinante sem o éxon 14 leva a sua retenção no núcleo celular (Eberhart et al, 1996;Willemsen et al, 1996;Tamanini et al, 1999;Davidovic et al, 2006), possivelmente devido à ausência do NES localizado neste éxon (Sittler et al, 1996). Mutagênese dirigida ao NES confirmou a necessidade deste para a localização citoplasmática da FMRP (Fridell et al, 1996;Bardoni et al, 1997;Hu et al, 2005;Ramos et al, 2006). Tanto a deleção apenas do éxon 14, quanto a mutagênese dirigida ao NES não avaliam a mudança de ORF causada pela exclusão do éxon 14 por splicing altertivo.…”
Section: I5 -Isoformas Da Fmrp Que Não Expressam O éXon 14 Do Fmr1unclassified